2018
DOI: 10.3390/molecules23061399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Activity and Cytotoxicity of Different Components of Natural Origin Present in Essential Oils

Abstract: Even though essential oils (EOs) have been used for therapeutic purposes, there is now a renewed interest in the antimicrobial properties of phytochemicals and EOs in particular. Their demonstrated low levels of induction of antimicrobial resistance make them interesting for bactericidal applications, though their complex composition makes it necessary to focus on the study of their main components to identify the most effective ones. Herein, the evaluation of the antimicrobial action of different molecules pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 55 publications
11
68
1
1
Order By: Relevance
“…As they often possess a broad spectrum of biological effects [13], EOs have potential in various applications for human, animal, and plant health, as well as food quality. Besides antimicrobial activity [14][15][16], EOs and their constituents have been observed to exhibit anaesthetic [17], antiparasitic [18], anti-inflammatory [19], antioxidant [20], antiulcer [21], antiviral [22], cytotoxic [23], immunomodulatory [24], insecticidal [25], and molluscicidal [26] properties. Despite their historical record as medicinal agents, European and American health authorities such as the European Pharmacopoeia and the United States Pharmacopoeia National Formulary list only a small number of EO-bearing plants and their preparations as medicinal [3].…”
Section: Volatile Antimicrobial Agents and In Vitro Methods For Evalumentioning
confidence: 99%
“…As they often possess a broad spectrum of biological effects [13], EOs have potential in various applications for human, animal, and plant health, as well as food quality. Besides antimicrobial activity [14][15][16], EOs and their constituents have been observed to exhibit anaesthetic [17], antiparasitic [18], anti-inflammatory [19], antioxidant [20], antiulcer [21], antiviral [22], cytotoxic [23], immunomodulatory [24], insecticidal [25], and molluscicidal [26] properties. Despite their historical record as medicinal agents, European and American health authorities such as the European Pharmacopoeia and the United States Pharmacopoeia National Formulary list only a small number of EO-bearing plants and their preparations as medicinal [3].…”
Section: Volatile Antimicrobial Agents and In Vitro Methods For Evalumentioning
confidence: 99%
“…; Garcia‐Salinas et al . ). Our findings suggest the potential use of both cinnamon oil and cinnamaldehyde for the topical treatment of infections in dogs, but the latter as a more promising bactericidal compound.…”
Section: Discussionmentioning
confidence: 97%
“…; Garcia‐Salinas et al . ). The anti‐inflammatory properties and wound healing application of cinnamon oil for soothing the pain resulted from microbial infection and inflammation have been identified (Han and Parker ).…”
Section: Introductionmentioning
confidence: 97%
“…Thymol, eugenol, and carvacrol have an antimicrobial effect against a broad spectrum of bacteria, namely Escherichia coli, Bacillus cereus, Listeria monocytogenes, Salmonella enterica, Clostridium jejuni, Lactobacillus sake, Staphylococcus aureus, and Helicobacter pyroli [15,22,23,26]. García-Salinas et al [46] found that the carvacrol, cinnamaldehyde, and thymol molecules contained in EOs could be used against E. coliand S. aureus-mediated infections, without a potential induction of bactericidal resistance and with lower cell toxicity. Other families of EO compounds also show antimicrobial properties: certain alcohols, aldehydes, ketones, monoterpene (geraniol, linalol, menthol, terpineol, thujanol, thujone, camphor etc.…”
Section: Discussionmentioning
confidence: 99%